High-resolution satellite-derived river network map reveals small Arctic river hydrography - Xin Lu; Kang Yang; Mia M Bennett; Chang Liu; Wei Mao; Ya Li; Wensong Zhang; Manchun Li (Environmental Research Letters, 2021)
Small rivers (width <30 m) are crucial components of Arctic terrestrial river networks. Yet to date, spatial resolution limitations of commonly used satellite imagery have inhibited quantification of their hydrography. By merging newly available Sentinel-2 multispectral satellite imagery with 2-m ArcticDEM digital elevation data, we created a continuous actively-flowing river network map of the Colville (Kuukpik) River Basin (∼36 000 km ^2 ) in Alaska, which includes small rivers as narrow as 10 m. We quantified the river hydrography (stream order and river width, length,surface area, velocity, slope, sinuosity, and catchment area) of the Colville river network in detail, revealing the dominant role of small rivers. Our results show that: (1) small rivers occupy >80% of total river length and surface area of the Colville river network and drain >90% of the catchment area; (2) including numerous small rivers increases the peak of hillslope-channel travel time distribution (TTD) by ∼4 times and shortens the mean hillslope-channel travel time by at least an order of magnitude compared to coarser-resolution river hydrography products; and (3) 87% of the Colville River Basin’s carbon dioxide is emitted from small rivers. In sum, we show that small Arctic rivers greatly influence streamflow TTD and carbon cycle. These findings expand our understanding of Arctic river hydrography to a 10-m spatial resolution and raise prospects for tracking dynamic surface water processes with high-resolution satellite observations.